ANALISIS GAYA KEPEMIMPINAN PADA PRAKTIK STUDI KELAYAKAN BISNIS DALAM ERA EKONOMI DIGITAL DI DAERAH PERBATASAN - Yeremia Niaga Atlantika; Sabinus Beni; Eligia Monixa Salfarini; Benedhikta Kikky Vuspitasari; Candra Gudiato (JURNAL LENTERA BISNIS, 2024)
This study aims to describe the leadership styles applied in the business evaluation process, specifically through business feasibility studies in the digital economy era. The research adopts a descriptive method with a qualitative approach. The study was conducted with informants from business actors in Bengkayang Regency, West Kalimantan. The informants included five individuals from agricultural, plantation, culinary, and service business clusters. The research shows that in the digital economy era, market aspects have become increasingly complex due to rapid changes in consumer behavior. Companies must adopt a comprehensive approach, utilizing digital data, social media, and big data to more accurately identify market segments and consumer preferences. High competition in the digital market demands adaptation and innovation to stay relevant. In the garment business, focusing on accurately identifying product demand is crucial, while service businesses, such as traditional clothing rentals, adjust marketing strategies based on consumer needs. Effective leadership in managing markets involves professionalism and active consumer participation. A participative leadership style proves effective in addressing complex business challenges.